2020
DOI: 10.1103/physrevaccelbeams.23.031001
|View full text |Cite
|
Sign up to set email alerts
|

Halo removal experiments with hollow electron lens in the BNL Relativistic Heavy Ion Collider

Abstract: A hollow electron beam has been proposed as an active control tool to remove the beam halo from highenergy, high-current hadron or ion machines (such as the High-Luminosity Large Hadron Collider). To study the halo removal rate and assess the effect on the ion beam core, one of the two electron lenses in the Relativistic Heavy Ion Collider was changed from a Gaussian beam profile to a hollow profile. We describe the design and verification of the hollow electron beam parameters as well as the methods to minimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…If the electron gyrofrequency is much larger than the plasma frequency and the typical frequencies of generated radiation then the permittivity tensor is close to the desired diagonal tensor. The successes noted above in the use of the hollow electron beams [5][6][7][8][9] allow us to hope for the successful use of the method proposed here to reduce the energy loss of bunches subjected to collimation. see Fig.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…If the electron gyrofrequency is much larger than the plasma frequency and the typical frequencies of generated radiation then the permittivity tensor is close to the desired diagonal tensor. The successes noted above in the use of the hollow electron beams [5][6][7][8][9] allow us to hope for the successful use of the method proposed here to reduce the energy loss of bunches subjected to collimation. see Fig.…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, new materials are considered for traditional collimator assembly [2] and alternative dielectric-based collimation systems are also discussed [3,4]. Moreover, the successful usage of hollow electron lenses (low-energy hollow electron beams) for efficient halo removal of intense high-energy beams in storage rings and colliders should be particularly mentioned [5][6][7]. It is equally important that similar hollow electron structures (called in that context the hollow plasma channels) were utilized recently in successful experiments on plasma wakefield acceleration [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Different beam tests have been performed and one of the main achievements was the successful demonstration that back-scattered electrons can be used to centre the electron beam around the circulating one. Moreover, measurements similar to those performed at Tevatron were repeated with 100 Z GeV Ru and 13.6 Z GeV Au beams, showing promising results not only in terms of halo removal, but also in terms of impact on the core, together with thorough investigations of hollow electron beam profile distortions and options to reduce them [38].…”
Section: Beam Energy [Tev]mentioning
confidence: 99%
“…It was found that random activation of the electron beam completely removes the proton halo beyond the electron beam inner radius on a timescale 𝑂(10 s). Very important are the parallel investigations of the proton beam halo and diffusion rates in the LHC beams at CERN [78], and the halo removal rates by hollow electron lens in the RHIC [79]. For the latter study, one of the two RHIC electron lenses was changed from a Gaussian beam profile to a hollow profile.…”
Section: S and Beyond: Electron Lenses In Lhc And Iota Future Directionsmentioning
confidence: 99%